Process Safety Management Expert System (PSMES) - Mohammad Faizal Bin Che Daud, Mohammad Faizal (Universiti Teknologi Petronas, 2009)
Unexpected releases of toxic, reactive, or flammable liquids and gases in processes involving highly hazardous chemicals have been reported for many years in various industries that use chemicals with such properties. Regardless of the industry that uses these highly hazardous chemicals, there is a potential for an accidental release any time they are not properly controlled, creating the possibility of disaster. To help ensure safe and healthful workplaces, OSHA has issued the Process Safety Management of Highly Hazardous Chemicals standard (29 CFR 1910.119), which contains requirements for the management of hazards associated with processes using highly hazardous chemicals. The objective of this project is to develop Process Safety Management Expert System (PSMES) (1). PSMES treats seven out of total of fourteen elements of Process Safety Management. PSMES is intended to serve as a tool to assist employers and employees in complying with the safety requirements. The tool is built using Visual Basic 2005 (Vb. net programming language). The project begin with the literature search on PSM. An expert system is software that attempts to provide an answer to a problem, or clarify uncertainties where normally one or more human experts would need to be consulted (2). This expert system will be a solution to the current Process Safety Management (PSM) weak point which its elements are treated separately, inconsistent, disintegrated and uncorrelated between one element to another. Early stage of the developing this tool starts with preparation of framework of each elements that are covered in scope of the project and to prepare all documents needed under each PSM elements to comply with OSHA requirements. The module is relevant to the current industry needs because it create a systematic approach to manage PSM in controlling the process hazards in the workplace especially in oil and gas industry like PETRONAS. The field test for this expert system is Natural Gas Dehydration Unit of Universiti Teknologi PETRONAS. This tool will be at its best fit for use, conformance to requirements and will able to satisfy the PSM implied needs. The expected outcome of this Process Safety Management Expert System (PSMES) is to replace the `paper based' conventional way in managing the PSM